Room escape at class: Escape games activities to facilitate the motivation and learning in computer science - Carlos Borrego; Cristina Fernández; Ian Blanes; Sergi Robles (OmniaScience, 2017)
Real-life room-escape games are ludic activities in which participants enter a room in order to get out of it only after solving some riddles. In this paper, we explain a Room Escape teaching experience developed in the Engineering School at Universitat Autònoma de Barcelona. The goal of this activity is to increase student's motivation and to improve their learning on two courses of the second year in the Computer Engineering degree: Computer Networksand Information and Security.